Описание классов комбинаторных конфигураций на основе отображений - Стоян, Ю.Г.; Гребенник, И.В. (Видавничий дім "Академперіодика" НАН України, 2008)
The problem of construction of formal descriptions of combinatorial sets based on primary combinatorial sets and proposed mappings is considered. A concept of composition k-image of combinatorial sets is introduced. A class of the composition k-images of combinatorial sets, k-compositions of permutations, is chosen and investigated. Some its properties are researched, and an example is given.